2010
DOI: 10.1002/jbio.200900095
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific opening of the blood‐brain barrier

Abstract: The blood-brain barrier (BBB) poses a significant impediment for the delivery of therapeutic drugs into the brain. This is particularly problematic for the treatment of malignant gliomas which are characterized by diffuse infiltration of tumor cells into normal brain where they are protected by a patent BBB. Selective disruption of the BBB, followed by administration of anti-cancer agents, represents a promising approach for the elimination of infiltrating glioma cells. A summary of the techniques (focused ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 80 publications
5
59
0
Order By: Relevance
“…Because selective and sufficient entry of drugs and their modification tools is important in CNS drug design, while still limiting the access of toxic compounds, knowledge about the BBB behaviour of drugs is highly researched (Chu et al 2006;Engelhardt 2006). Moreover, the addition of physical techniques to temporarily and spatial-selectively open the BBB, can even further extend the clinical possibilities (Campbell et al 2011;Liu et al 2010;Madsen and Hirschberg 2010;Rossi 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Because selective and sufficient entry of drugs and their modification tools is important in CNS drug design, while still limiting the access of toxic compounds, knowledge about the BBB behaviour of drugs is highly researched (Chu et al 2006;Engelhardt 2006). Moreover, the addition of physical techniques to temporarily and spatial-selectively open the BBB, can even further extend the clinical possibilities (Campbell et al 2011;Liu et al 2010;Madsen and Hirschberg 2010;Rossi 2011).…”
Section: Introductionmentioning
confidence: 98%
“…So, the traditional explanation of anti-cancer PDT e®ect is However, several studies show that PDF increases the BBB permeability temporally. [67][68][69][70] Hirschberg et al using 400 m bare°at-end quartz¯ber (635 nm) and stereotaxic procedure clearly show that the ALA-PDT causes the opening of BBB. At the low°uence levels of 9L, the ALA-PDT opens the BBB rapidly without any damages of brain tissues, the disrupted BBB is observed during 2 h following PDT and restored during the next 72 h. 67 The disruption of BBB is greater using the higher°uence level of 26 J but the damages of surrounding tissues (necrosis, edema, hemorrhage) are observed for 17 days.…”
Section: Photodynamic Therapy As a Potential Tool For Brain Drug Delimentioning
confidence: 99%
“…7). [68][69][70] The nanoparticles show great promise for PDT. 75 Madsen et al in experiment in vivo showed that PDT (the photosensitizer - Despite the promising e®ect of PDT on the transportation of macrophages through the BBB, there is an important question: \How the brain cleans from gold nanoparticles and is it possible to use this procedure for human?…”
Section: Photodynamic Therapy As a Potential Tool For Brain Drug Delimentioning
confidence: 99%
“…[19] In low-grade gliomas, BBTB resembles BBB, while in high-grade gliomas, BBTB becomes disrupted and "leaky," characterized by major alterations of the normal vascular function manifested by contrast-enhanced MRI by Dhermain et al [19,26] However, the magnitude of this disruption is unlikely sufficient to allow drug penetration in therapeutically meaningful quantities, and thus BBTB remains a major obstacle for brain drug delivery. [27,28] …”
Section: The Blood-brain Barrier: the Brain's Protection Systemmentioning
confidence: 99%